LEVANTAMENTO DAS CONDIÇÕES DE USO DOS PASSEIOS EM UMA DETERMINADA ÁREA NO CENTRO DO MUNICIPIO DE IJUÍ - Bohn, Tiago R.; Herrmann, Thiana D.; Bellé, Joana P.; Specht, Luciano P.; Gass, Sidnei L. B. (Salão do Conhecimento, 2013)
Resumo